Novel correlation to evaluate the pressure losses for different traffic jam conditions in road tunnel with alternative jet fan, second part. (February 2020) - Musto, Marilena; Cascetta, Furio; D'Alessandro, Carmine; De Maio, Davide; Rotondo, Giuseppe
Highlights: Novel correlation for pressure loss in road tunnel for alternative ventilation system. Authors provide a kind of "friction factor" due to vehicles as function of FTT. The innovative approach reproduces the interaction between the cars and the air jet outflow. Correlation percentage error is about of 3.3 (for FTT > 0.2) with respect to CFD results. Abstract: The aim of this study is to provide a novel correlation to evaluate the pressure loss, in road tunnel, for different traffic jam conditions (Filling Tunnel Traffic, FTT). The proposed correlation refers to a longitudinal ventilation system of innovative impulsive jet fan with silencers inclined toward tunnel floor. This innovative design solution reduces the Coanda effect and, consequently, the pressure loss, requiring thereby less electrical power with respect to the traditional one. The jam vehicles, equally spaced, are considered as asperities whereby, the correlation provides a kind of "friction factor" due to vehicles as function of FTT. The pressure loss caused by vehicles depends on the roughness and aerodynamic coefficient of vehicles surface and depends also on vortices between the vehicles. This "friction factor" can be used to compute the pressure loss due to vehicles and added to the wall friction, providing the "total friction factor". The novel correlation, here proposed, is useful to the designer to size the innovative ventilation system because there are no data in literature or in technical reports about the interaction between the air flux ejected from the inclined jet fan and cars. This work is the extension of an antecedent one (Cascetta et al., 2019) in which the novel correlation has referred to a longitudinal ventilation system equipped with traditional impulsive jet fan.